Optimalisasi Komunikasi Organisasi Dalam Penguatan Eksistensi Kelembagaan Dewan Energi Nasional - Mandala, Agung; Toni, Ahmad (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Sekolah Tinggi Ilmu Sosial dan Ilmu Politik (STISIPOL) Candradimuka, 2024)
Powering the country's energy strategy is the impartial and everlasting National Energy Council. The Energy Law 30 of 2007 constituted the legal basis for the formation of DEN. The seven ministers directly responsible for energy supply, transportation, distribution, and consumption make up DEN, which is led by the President of the Republic of Indonesia and represented by the Vice President of the Republic of Indonesia. Public Relations'